Fantasy Animals and Explorative Learning: Projects in Second Language Acquisition (KULT_online, 2013)
The concept of Task-Based Language Learning (TBLL) is very popular in all second-language acquisition pedagogies because it enables the learner to use the new language in authentic and relevant situations. With this book, Rainer E. Wicke gives an overview of the development of the concept of TBLL in the Anglo-American discussion as well as in Germany. In addition it presents some projects from his work as a language teacher which illustrate the use of TBLL. The book does not give a complete overview of TBLL in German as a foreign language, but describes some inspiring projects for the foreign language classroom.